Stability Analysis of Geotextile Reinforced Marine Causeways - Heba Koura; Ehab Tolba; Elsayed Galal (Port Said Engineering Research Journal, 2020)
The use of geotextile tubes as retaining systems, geotechnical application, and coastal protection in temporary and permanent structures is gaining lots of concern throughout the recent decades. In the present study, computer software, ABAQUS, was used to investigate the stability of geotubes as soil retaining structure for marine causeway. Nine scenarios comprised of two geotubes lining the side of a 1:1 slope causeway were modeled to explore their effect on the causeway displacement under surcharge loads. The stability of the system was investigated through using different deformed shapes of geotubes. These deformed shapes were obtained by using different pumping pressures (0.0, 5.0, and 20.0 kPa). Moreover, the effect of tidal range was studied by defining different water depths (0.5, 1.5 and 2.5 m measured from the causeway toe). The results showed that the use of geoextile tubes subjected to pumping pressure of 0.0 and 5.0 kPa improves the deformation behavior of the causeway with water depths of 0.5 and 1.5 m. While, the deformation was aggravated with water depth of 2.5 m when using geotextile tubes subjected to pumping pressures of 0.0 , 5.0 , and 20.0 kPa. On the other hand, the model ceased when applying pumping pressure of 20.0 kPa with water depths of 0.50 and 1.50 m due to the failure of the upper tube. Therefore, it is recommended to use the geotextile tubes subjected to pumping pressure of 0.0 and 5.0 kPa in case of lower water depths only.